Health Behaviors, Food Purchasing, and Meal Preparation in a Sample of South Asian Adults in America: A Pilot Study. (7th June 2021) - Murphy, Bridget; Talegawkar, Sameera; Mohsin, Farhan; Lal, Supriya; Harris, Samantha; Blatt, Mia; Parekh, Niyati
Abstract: Objectives: South Asians are the fastest growing ethnic population in the United States (U.S.). However, there remains a dearth of culturally relevant diet research in this ethnic minority. examining South Asians living in the U.S. Our objective was to assess health behaviors, food purchasing, and meal preparation habits of in a convenience sample of South Asian adults living in the U.S. Methods: For this pilot study, adults aged ³18 years who self-identified as South Asian and living in the U.S. were recruited via e-mail and social media platforms ( n = 66). Information on socio-demographics, household food security, food shopping and meal preparation, smoking, physical activity, and alcohol consumption was collected via a Qualtrics survey using a virtual platform. Results: Respondents had a mean age of 29.8 years (±8.6), were mostly female (82%), and had earned a Bachelor's degree or higher (91%). Respondents lived across the U.S., with 65% in the Northeast region. Approximately 88% of respondents met criteria for being food secure. Sixty-nine % of people surveyed reported eating or preparing South Asian meals at home 3 or more times per week and 75% reported living near a South Asian food store and visiting it 1–2 times per month. Participants reported sharing food purchasing responsibilities with a spouse or another family member, but were the primary person preparing food in the household. A majority of participants never smoked (91%) and 39% reported never drinking alcohol. Most participants (85%) reported always or very often using South Asian herbs and spices (such as cumin, coriander, garam masala, and turmeric) in their cooking. Conclusions: Most respondents in this pilot study of South Asians living in the U.S. maintained culturally relevant culinary practices, including South Asian meal preparation and consumption and regular use of herbs and spices. Results from this survey will provide a greater context of health behaviors; the food purchasing and meal preparation data will provide a framework for the development of culturally inclusive diet assessment tools that incorporate traditional and western food items, including herbs and spices that are often absent in current tools. Funding Sources: None.